Զարդանախշը հայկական գրքարուեստում - Ամիրջանեան, Լիլիթ; Վարդանեան, Արման (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье проанализированы роль и значение главного элемента орнаментального искусства-орнамента в сфере развития армянских культурных памятников, в частности, средневекового армянского книжного искусства. Представлены способы построения и изображения, а также символика орнамента в средневековом книжном искусстве. В статье говорится об особом теологическом, философском, эстетическом смысле и семантики орнаментов, мотивов, а также их цветов, проявленных в абстрактных знаках (символах) и связанных с идейным содержанием соответствующего письма на оригинальных страницах Священных Книг. The article analyzes the role and significance of the ornament, main element of ornamental art, in the sphere of development of Armenian cultural monuments, in particular, medieval Armenian book art. The methods of construction and depiction and the symbolism of the ornament in medieval book art are also presented. The article speaks about the special philosophical, aesthetic meaning and significance of ornaments, motifs, as well as their colors, manifested in abstract signs (symbols), related to the ideological content of the corresponding letter on the original page of the Scriptures.
Keywords: Հաղորդումներ; Հայկական զարդարվեստ